2012 2nd International Conference on Consumer Electronics, Communications and Networks (CECNet) 2012
DOI: 10.1109/cecnet.2012.6201712
|View full text |Cite
|
Sign up to set email alerts
|

Ku-band filters using open-loop and quarter-wavelength resonators based on LTCC technology

Abstract: A novel Ku-band single layer bandpass filter using open-loop and quarter-wavelength resonators based on LTCC technology is proposed. A pair of transmission zeros is introduced by the cross coupling, which can improve the attenuation near the passband. The size of the filter is about 6mm × 6mm × 0.288mm, about 0.75 g × 0.75 g . To reduce the filter's size, a modified filter with multilayer structure is designed. It has a center frequency of 15.4 GHz with bandwidth of 800 MHz, a size of only 0.75 g × 0.5 g . Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The improved BPF has a size of 6 × 6 mm 2 (including 50‐Ω feed lines), which is compact amounting to approximately 0.52 λ g × 0.52 λ g , where λ g is the guide wavelength at 17 GHz. Comparing with other similar works presented in the Table , it is shown that the improved BPF in this work has better rejection at upper stopband and smaller size.…”
Section: Improved Filter Designing To Enhance the Selectivitysupporting
confidence: 59%
See 1 more Smart Citation
“…The improved BPF has a size of 6 × 6 mm 2 (including 50‐Ω feed lines), which is compact amounting to approximately 0.52 λ g × 0.52 λ g , where λ g is the guide wavelength at 17 GHz. Comparing with other similar works presented in the Table , it is shown that the improved BPF in this work has better rejection at upper stopband and smaller size.…”
Section: Improved Filter Designing To Enhance the Selectivitysupporting
confidence: 59%
“…Measured results show the improved BPF have good selectivity and wide stopband, so that it can be used for wireless communication and radar applications. [9] 2.54% -0.5k g by k g [10] 5.2% 16-38 GHz 0.75k g by 0.5k g This work 17.3% 22.6-50 GHz 0.53k g by 0.53k g…”
Section: Resultsmentioning
confidence: 81%